Contraceptive Utilisation Among Mothers of Reproductive Age in Ajman, United Arab Emirates - Kanwal, Naila (Sultan Qaboos Univ Med J, 2017)
OBJECTIVES: This study aimed to determine contraceptive utilisation among mothers aged 18–49 years old in Ajman, United Arab Emirates (UAE). METHODS: This cross-sectional study was carried out from May to November 2013. A total of 400 participants were recruited from two primary healthcare centres and one private hospital in Ajman. An interviewer-administered validated questionnaire was used for data collection. RESULTS: The frequency of previous and current contraceptive use was 68.0% and 61.8%, respectively. Expatriates more frequently used contraceptives in comparison to Emiratis (77.3% versus 54.3%, respectively). Contraceptive use increased significantly with age (75.5% among >35-year-olds versus 57.3% among ≤25-year-olds; P <0.050) and education level (83.3% among postgraduates versus 60.0% among those with primary education; P <0.050). In addition, contraceptive use was significantly higher among those living in a nuclear family system (P <0.050). A univariate analysis indicated significant associations between contraceptive use and age, nationality, education level, type of family system, employment sector, parity, knowledge of birth control measures and source of birth control information (P <0.050 each). However, no significant associations were found via multivariate analysis. CONCLUSION: Healthcare practitioners can play a pivotal role in providing contraceptive advice which could lead to an improvement in contraceptive utilisation. Efforts are recommended to raise awareness regarding newer forms of contraceptives among mothers of reproductive age in the UAE.